Who deserved the 2008-2009 Belgian football champion title? A semiparametric answer - Geenens, G. (Journal of Quantitative Analysis in Sports, 2010)
Football (soccer) is certainly the most popular sport in Belgium. In 2008-2009, the Belgian premier league (the so-called Jupiler Pro League) consisted of 18 teams, each having played others twice, home and away. Wins and draws earned 3 points and 1 point, respectively, and teams were first ranked by total points and then by total wins, regardless of the goal difference (or the number of goals scored), unlike in most European leagues. Obviously, the Belgian Champion should have been the team which had ended the season on top of the ranking, but a very unlikely event happened: the first two teams, Sporting Anderlecht and Standard Liege, completed the season with exactly the same number of points (77) and the same number of victories (24). Although the goal difference was in favor of Anderlecht, an extraordinary playoff match was hastily organized to decide the championship, and Standard ended up winning. That dramatic denouement sustained the discussions among the large football-lover part of the Belgian population and opens the interrogation: which team was really the best? The aim of this work is to objectively investigate this question through statistical modelling. Given the results of the whole season, a semiparametric model for the conditional probabilities of home win, tie and away win for each match, given the involved teams and other explanatory variables, is fit. The semiparametric nature of the model grants a great flexibility and allows us to identify interesting and up to now ignored patterns in the above probabilities. Then, a large number of Monte-Carlo simulations are run as if the season was replayed a large number of times, which permits the estimation of absolute probabilities of many events of possible interest. In particular, clear evidence about which team really deserved the 2008-2009 Belgian football champion title appears.